HEART FAILURE WITH A REDUCED EJECTION FRACTION ("SYSTOLIC HF") - Hozhiev B. B. (Web of Journals Publishing, 2024)
The article presents heart failure (HF) with a reduced ejection fraction or syndrome of ventricular dysfunction of the heart. Left ventricular failure leads to the development of shortness of breath and fatigue, right ventricular failure leads to peripheral edema and fluid accumulation in the abdominal cavity. Both ventricles or each ventricle separately may be involved in the process. The diagnosis is established clinically, confirmed by chest X-ray data, echocardiography and levels of natriuretic peptides in blood plasma.
Keywords: Left ventricular failure, angiotensin converting enzyme, pacemakers, defibrillators.